Body Mass Index, Haemoglobin, and Total Lymphocyte Count as a Surrogate for CD4 Count in Resource Limited Settings. (18th April 2017) - Kwantwi, Louis Boafo; Tunu, Bismark Kwame; Boateng, Daniel; Quansah, Dan Yedu
Abstract : Background . In view of the lack of evidence on the possibility of an economically viable, easy, and readily available biomarker to substitute the traditional role of CD4 counts in HIV disease progression, this study seeks to investigate the potential use of body mass index (BMI), haemoglobin (Hb), and total lymphocyte count (TLC) as surrogate biomarkers for monitoring the disease. Methods . This cross-sectional study was undertaken at the antiretroviral clinic (ART) of the Bomso Hospital, Kumasi, Ghana. We recruited 384 individuals who were 18 years or older and confirmed HIV seropositive patients. Blood samples were assayed for TLC and Hb. Weight and height were determined and BMI was calculated. Result . At a cut-off point of 12.15 g/dL, Hb had sensitivity and specificity of 73.9% and 56.8%, respectively, whereas BMI had 69.6% and 80.1% sensitivity and specificity, respectively. The sensitivity and specificity were also 100% among the studied participants at a cut-off point of 1200 mm −3 for TLC. There was a significant positive correlation between CD4 count and Hb (rho 0.262, p = 0.0001 ), BMI (rho 0.301, p = 0.0001 ), and TLC (rho 0.834, p = 0.0001 ). Conclusion . The study demonstrates that TLC, Hb, and BMI may provide some useful prognostic information independent of that provided by CD4 count.